Treatment of D-galactose-induced rat polycystic ovarian condition using Lepidium sativum and secondary antibodies (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: There is still much to be discovered regarding the etiopathogenesis and management of polycystic ovarian syndrome (PCOS).Materials and Methods: Four groups of female Wister-Albino rats were established, each with a normal estrous cycle: control, D ( + ) galactose (D-galactose), Lepidium sativum (L. sativum), and prepared secondary antibody (Ab2). Serum samples were collected, and histopathological examination was performed on ovaries and spleen tissues. Immunoreactive anti-ovarian antibody (AOA) quantities were determined using a modified antigen-based ELISA procedure. ELISA assay kits were used to quantify FSH, LH, and estradiol 17 β concentrations.Results: The study found that AOA concentration in undiluted samples was significantly higher in the second and fourth weeks after PCOS induction by D-galactose (p < 0.001). However, antibody index% and titer elevated in the D-galactose group. L. sativum’s late efficacy was observed in the fourth week, while the concentration of undiluted samples in the D-galactose + Ab2 group lowered (p < 0.001). Higher basal FSH and LH levels and lower estrogen levels are associated with PCOS development. L. sativum’s immunomodulatory properties may contribute to this association. Estradiol-17ß concentrations increased in D-galactose + L. sativum and D-galactose + Ab2 groups, respectively.Conclusion: Careful extrapolation of experimental models is crucial for clinical applications, as technical advancements make Ab2 production easier. Further study is needed to fully understand its potential in immunotherapy.Adv. Vet. Anim. Res., 11(2): 418-428, June 2024http://doi.org/10.5455/javar.2024.k791